COVID-19 and medical educator perceptions: Sense-making during times of crisis - L Govender; C Jacobs (African Journal of Health Professions Education, 2022)
Background. Although crises are generally considered uncommon, health professions education (HPE) literature gives evidence of repeated and ongoing crises. This has been most recently demonstrated by the global impact of COVID-19. Crisis management literature proposes that such recurrent crises are opportune moments for learning. While there has been much literature published that describes changes made to the format of HPE amid COVID-19, there has been little attention given to the perceptions of medical educators. Medical educators’ experiences may serve as a resource to uncover lessons that may have been learnt during this period.